2006
DOI: 10.1021/jm060804a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of 2-(3‘,4‘,5‘-Trimethoxybenzoyl)-3-Amino 5-Aryl Thiophenes as a New Class of Tubulin Inhibitors

Abstract: 2-(3',4',5'-Trimethoxybenzoyl)-3-amino-5-aryl/heteroaryl thiophene derivatives were synthesized and evaluated for antiproliferative activity, inhibition of tubulin polymerization, and cell cycle effects. SARs were elucidated with various substitutions on the aryl moiety 5-position of the thienyl ring. Substituents at the para-position of the 5-phenyl group showed antiproliferative activity in the order of F=CH(3) > OCH(3)=Br=NO(2) > CF(3)=I > OEt. Several of these compounds led to arrest of HL-60 cells in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 20 publications
0
26
0
Order By: Relevance
“…More and more derivatives have been demonstrated to present obvious antimicrobial, antitumor, antifungal activity, etc. [34][35][36][37][38][39][40][41][42] Hence, as part of our agrochemistry program aimed at the search for novel natural product-oriented bioactive molecules, based on the aforementioned, we utilized blactam scaffold as prototype structural unit and planed for the incorporating natural gallic acid and azetidinone moieties in a single molecular scaffold (Fig. 2).…”
Section: Introductionmentioning
confidence: 99%
“…More and more derivatives have been demonstrated to present obvious antimicrobial, antitumor, antifungal activity, etc. [34][35][36][37][38][39][40][41][42] Hence, as part of our agrochemistry program aimed at the search for novel natural product-oriented bioactive molecules, based on the aforementioned, we utilized blactam scaffold as prototype structural unit and planed for the incorporating natural gallic acid and azetidinone moieties in a single molecular scaffold (Fig. 2).…”
Section: Introductionmentioning
confidence: 99%
“…The role of halogen substitutions has been extensively discussed in the literature. Different authors have found that K d or IC 50 values improve up to a point in which a further increase in van der Waals radius brings a significant decrease in affinity (4–13). The breaking point occurs at different van der Waals radii (i.e.…”
mentioning
confidence: 99%
“…2-Amino-3-(2-benzylidene-6-bromocyclohexylidene)prop-1-ene-1,1,3-tricarbonitrile (7). -A solution of compound 2 (0.30 g, 1 mmol) in glacial acetic acid (30 mL) was warmed to 60 o C, then bromine solution (0.16 g, 1 mmol) in acetic acid (10 mL) was added dropwise under continuous stirring.…”
Section: -(Aminomentioning
confidence: 99%